Propriedades físico-hídricas de latossolos sob plantio direto e sua relação com a trabalhabilidade - Broch, Djulia Taís (2019)
The soil is the main substrate used by plants, becoming important the knowledge of water storage and the relationship with the attributes of the soil. Sowing under inadequate moisture conditions can result in the adherence of the soil to implement devices, changing the sowing depth and developing problems in the establishment of the crop. Knowledgement about soil workability can reduce the risk of degradation of it and the energy required for the machine operations. The go of this research was to set a relationship between physical-hydrological properties and the workability of LATOSSOLOS (oxisol) conducted under no-tillage. Samples with preserved and not preserved structure were collected at five depths of five soils in Rio Grande do Sul (BR), under no-tillage system. Particle size, organic matter (MO), soil density (DS), maximum soil density (Dsmax), relative density (DR), the moisture on the field capacity (CC) and permanent wilting point (PMP), total porosity (PT) and the distribution of the pores diameter, soil consistency, water retention curve, optimal water range (IHO), water content of the soil where adhesion occurs and germination of soybean seeds. The results proved that the collected soils show different granulometric compositions and organic matter contents. The values obtained for the DS range were 1,167 to 1,660 g / cm³, therefore higher DR values found, indicated soil compaction. Higher penetration resistance (RP) values provide a lower limit than decreased IHO. Soils with more sand in their composition retain less water, while the clay ones showed greater retention. The optimal compaction moisture (UOC) increased with clay soils and MO content. The soil water content, where soil adherence at the seeding device began, had a range of 0.236 to 0.340 g / g among the studied soils, which was influenced by clay and MO contents. The soil moisture that occurred soybean seeds germination ranged from 0.150 to 0.302 g / g, being influenced by the clay content. The physical-hydrological properties are related to soil workability. The UOC is lower than the adherence and might be observed to establish a proper sowing window.